Friendlessness and theory of mind: A prospective longitudinal study. (2nd September 2014) - Fink, Elian; Begeer, Sander; Peterson, Candida C.; Slaughter, Virginia; de Rosnay, Marc
<x xml:space="preserve">Abstract</x> Chronic friendlessness in childhood predicts adverse mental health outcomes throughout life, yet its earliest roots are poorly understood. In theory, developing a theory of mind (ToM) should help children gain mutual friends and one preschool study (Peterson & Siegal, 2002. Br J Dev Psychol, 20, 205) suggested a cross‐sectional connection. We therefore used a 2‐year prospective longitudinal design to explore ToM as a predictor of mutual friendship in 114 children from age 5 to 7 years after controlling potential confounds including language ability and group popularity. Confirming friendship's distinctiveness from group sociometric status, numerous group‐rejected children (53%) had a mutual friend whereas 23% of those highest in group status did not. Five‐year‐olds with a mutual friend significantly outperformed their friendless peers on a comprehensive ToM battery (basic and advanced false belief). Longitudinally, chronically friendless 7‐year‐olds (no friends at either testing time) stood out for their exceptionally poor Time 1 ToM understanding even after controlling for group popularity, age, and language skill. Extending previous evidence of ToM's predictive links with later social and cognitive outcomes, these results for mutual friendship suggest possible interventions to help reduce the lifelong mental health costs of chronic friendlessness.